Variability of hydro-physical properties in drained peat soil: A case study of Perigi Village, Ogan Komering Ilir, South Sumatra, Indonesia - Imanudin, Momon Sodik; Bakri, Bakri; Prayitno, Muh. Bambang; Sazili, A.; Choi, Eunho (Journal of Degraded and Mining Lands Management, 2026)
Peatlands have a hydrological function, providing water, controlling floods and weather conditions, and regulating chemical and biological processes in the soil. Among the most important hydrological parameters indicating peatland damage are soil hydraulic conductivity (Ks), bulk density, and porosity. This study aimed to determine the diversity of soil hydraulic conductivity values in peatlands reclaimed for agriculture. Soil sampling was carried out in the peatlands of Perigi Village, included in the Sugihan-Saleh KHG (Peat Hydrological Area). The Ks measurement method in the laboratory uses the constant head method. The research results showed that the vertical permeability coefficient (kv) was 50.21-52.63 cm/h and the horizontal permeability coefficient (kh) was 113.2 cm/h. Spatial variations did not show significant differences, and the Ks value relative to the distance to the drainage channel shows the same inhibiting value of 50.21-52.63 cm/h. Soil porosity values ranged from 92.10 to 95.34%, and soil bulk weights ranged from 0.12 to 0.23 g/cm3. This condition shows that horizontal water movement is very fast and this causes a rapid decrease in the water level if the land is opened up by building channels. Therefore, assessing damage to peatland also determines the number of land drainage networks that have been built. To control the groundwater level so that it does not fall quickly and in accordance with the compliance figure of 40 cm, the construction of canal blocking is absolutely necessary in the drainage system in agricultural and plantation areas.